KODE ETIK JURNALISTIK: HAK TOLAK, EMBARKO DAN OFF THE RECORD SEBAGAI HAK NARASUMBER - Hamson, Zulkarnain; Mahi, Faizah; Mukhlishah, Nurul; Herawati, Herawati (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
The journalistic code of ethics is very important because it functions as a guide for journalists in carrying out their duties. There are several main reasons why a journalistic code of ethics is very important: a) Maintaining Public Trust: A code of ethics helps journalists maintain integrity and credibility in conveying information, so that the public continues to trust the media; c) Preventing the Spread of Hoax News: By adhering to the principles of accuracy, verification and balance, journalists can avoid the spread of fake news or hoaxes that can mislead the public; d) Upholding Objectivity and Neutrality: The code of ethics emphasizes the importance of being impartial in news coverage, so that the information conveyed is not influenced by certain interests; e) Protecting Human Rights and Privacy: The code of ethics prevents journalists from spreading information that violates someone's privacy rights or harms certain parties without clear and justifiable reasons; f) Avoid Abuse of Media Power: The media has great power in shaping public opinion. The code of ethics aims to ensure that this power is not misused for personal, political or certain group interests; g) Guarantee Professionalism in Journalism: The code of ethics establishes high standards for journalists in their work, so that this profession remains respected and appreciated by society. This workshop was attended by 14 journalists, taking place in Makassar City, attended by 14 Readtimes.id journalists, guided by the Chief Editor (Pimred), with the sole speaker Zulkarnain Hamson